Clinical applicability of short form of Bruininks-Oseretsky Test of Motor Proficiency Second Edition in patients after treatment of acute lymphoblastic leukemia - Šnajdrová, Tereza; Patrmanová, Eliška; Jevič, Filip; Bořilová, Karolína; Hrdoušková, Monika; Musálek, Martin (Frontiers in Pediatrics, 2023)
Introduction: Acute lymphoblastic leukaemia (ALL) ranks among paediatrics' most common oncological malignancies. Monitoring motor performance levels associated with self-sufficiency in the everyday activities of ALL patients is extremely important during treatment. The motor development of children and adolescents with ALL is most often assessed using the Bruininks Oseretsky Test of Motor Proficiency Second Edition (BOT-2) complete form (CF) with 53 items or the short form (SF) with 14 items. However, there is no evidence in research that BOT-2 CF and SF give comparable results in the population of patients with ALL. Objective: This study aimed to determine the compatibility of motor proficiency levels achieved from BOT-2 SF and BOT-2 CF in ALL survivors. Materials and Method: The research sample consists of n = 37 participants (18 girls, 19 boys) aged 4-21 years (10.26, ± SD 3.9) after treatment for ALL. All participants passed BOT-2 CF and were at least 6 months and a maximum of 6 years from the last dose of vincristine (VCR). We used ANOVA with repeated measures, considering the sex, intra-class correlation (ICC) for uniformity between BOT-2 SF and BOT 2 CF scores and Receiving Operating Characteristics. Results: BOT-2 SF and BOT-2 CF assess the same underlying construct, and BOT-2 SF and CF standard scores have good uniformity: ICC=0.78 for boys and ICC=0.76 for girls. However, results from ANOVA showed that the participants achieved a significantly lower standard score in SF (45.1 ± 7.9) compared to CF (49.1 ± 9.4) (p < 0.001; Hays ω2 = 0.41). ALL patients performed the worst in Strength and Agility. According to the ROC analysis, BOT‑2 SF obtains acceptable sensitivity (72.3 %) and high specificity (91.9 %) with high accuracy of 86.1 %, and the fair value of the Area Under the Curve (AUC) =0.734 CI95 % (0.47 ‑ 0.88) in comparison to BOT‑2 CF. Conclusions: To reduce the burden on ALL patients and their families, we recommend using BOT 2 SF instead of BOT-2 CF as a useful screening tool. BOT SF can replicate motor proficiency with as high a probability as BOT-2 CF but systematically underestimates motor proficiency.